Influence of temperature on the bending stiffness and tensile-shear strength of composite–metal joints. Issue 14 (6th December 2018) - Reis, J.M.L.; Andrade, B.; Watanabe, M.M.; da Costa Mattos, H.S.
ABSTRACT: The temperature effect on bending and shear strength of single lap joints, composed by metal–composite substrates with fixed geometry, was evaluated in this paper. The tests provide analysis associated with a system frequently used in the oil and gas industry, characterized by the use of polymeric composite materials with adhesives for repairing and reinforcing pipelines. The results revealed that the tensile behavior of the composite is highly affected by temperature and can be predicted by a linear function with good agreement. The bending stiffness and tensile-shear strength of composite–metal single lap joints are also dependent of the test temperature. The first can be represented by a linear equation and the second by a power law, both with good agreement.